Health promotion among military police officers: The importance of vaccination in the prevention of diphtheria and tetanus (Research, Society and Development, 2025)
Vaccination is one of the main strategies for promoting health and preventing vaccine-preventable diseases. This study addresses the importance of the dT vaccine in protecting against diphtheria and tetanus among military police officers, a group frequently exposed to injuries and contaminated environments. The objective was to raise awareness among military police officers about the relevance of immunization against diphtheria and tetanus, stimulating preventive behaviors and strengthening the vaccination culture in the workplace. The methodology consisted of a qualitative and descriptive educational action, involving a lecture, distribution of brochures, and display of an informative banner in a Military Police battalion. Forty-five police officers participated, whose reports and observations demonstrated increased knowledge and interest in immunization against diphtheria and tetanus. The results showed greater adherence to prevention and intention to seek health units. It is concluded that health education is an effective tool to strengthen the vaccination culture and promote the well-being of military police officers.